Gambaran Budaya Pemberian MP-ASI di Desa Mundu Pesisir Kabupaten Cirebon - Rt. Zulfa Nur Azzah; Ermiati Ermiati; Nenden Nur Asriyani Maryam (stikes dharma husada bandung, 2018)
The cultural of early complementary feeding in infants is very risky because in the ages of < 6 months old, the digestive system of a baby has not matured completely. However, this culture is still widely practiced in the Desa Mundu Pesisir, where the reports of the puskesmas showed 87.17% of the babies in the village have been given early complementary feeding. This study aims to find out the description of the culture of giving complementary feeding in Desa Mundu Pesisir Kabupaten Cirebon. The study design used was quantitative descriptive method with a random sampling technique that was done on 94 mothers with children aged between 6-24 months. The instruments used in this study was questionnaires made by the researcher. The method was tested for its validity by experts in the maternity field and was declared valid with a range of 0,450-0,773 and reliable with a value of 0,702. The research was carried out from April 2018 to May 2018 in Desa Mundu Pesisir. The results of this research has indicated that the culture of early complementary feeding that is still being carried out are by giving banana (73,4%), giving milk porridge and applying honey onto the baby’s hard palate (62,8%), mothers who did not consume chili (58,5%) and mothers who did not consume shrimp (56,4%) during breastfeeding. Meanwhile the culture that has been abandoned is giving crushed food (87,2%), the giving of air tajin (75,5%), giving of herbal medicine in cekok and early nyapih (76,6%). Based on the results obtained, it can be concluded that the infants in Desa Mundu Pesisir are at risk of developing gastrointestinal disorders because of early complementary feeding. A strategy using appropriate media is therefore needed to change the maternal behavior pattern